Improved Energy Supply Regulation in Chronic Hypoxic Mouse Counteracts Hypoxia-Induced Altered Cardiac Energetics - Calmettes, Guillaume (Public Library of Science, 2010)
BACKGROUND: Hypoxic states of the cardiovacular system are undoubtedly associated with the most frequent diseases of modern time. Therefore, understanding hypoxic resistance encountered after physiological adaptation such as chronic hypoxia, is crucial to better deal with hypoxic insult. In this study, we examine the role of energetic modifications induced by chronic hypoxia (CH) in the higher tolerance to oxygen deprivation. METHODOLOGY/PRINCIPAL FINDINGS: Swiss mice were exposed to a simulated altitude of 5500 m in a barochamber for 21 days. Isolated perfused hearts were used to study the effects of a decreased oxygen concentration in the perfusate on contractile performance (RPP) and phosphocreatine (PCr) concentration (assessed by (31)P-NMR), and to describe the integrated changes in cardiac energetics regulation by using Modular Control Analysis (MoCA). Oxygen reduction induced a concomitant decrease in RPP (−46%) and in [PCr] (−23%) in Control hearts while CH hearts energetics was unchanged. MoCA demonstrated that this adaptation to hypoxia is the direct consequence of the higher responsiveness (elasticity) of ATP production of CH hearts compared with Controls (−1.88±0.38 vs −0.89±0.41, p<0.01) measured under low oxygen perfusion. This higher elasticity induces an improved response of energy supply to cellular energy demand. The result is the conservation of a healthy control pattern of contraction in CH hearts, whereas Control hearts are severely controlled by energy supply. CONCLUSIONS/SIGNIFICANCE: As suggested by the present study, the mechanisms responsible for this increase in elasticity and the consequent improved ability of CH heart metabolism to respond to oxygen deprivation could participate to limit the damages induced by hypoxia.